2020
DOI: 10.3390/nano10040735
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Hydrolysis of Bacterial Cellulose for the Production of Nanocrystals for the Food Packaging Industry

Abstract: Bacterial cellulose nanocrystals (BCNCs) obtained by enzymatic hydrolysis have been loaded in pullulan biopolymer for use as nanoparticles in the generation of high-oxygen barrier coatings intended for food packaging applications. Bacterial cellulose (BC) produced by Komagataeibacter sucrofermentans was hydrolyzed by two different enzymatic treatments, i.e., using endo-1,4-β-glucanases (EGs) from Thermobifida halotolerans and cellulase from Trichoderma reesei. The hydrolytic activity was compared by means of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
2
10
0
1
Order By: Relevance
“…These results are supported by previous scientic research, [46][47][48] and ascribed to water molecules competing for the -OH groups displaced along both the biopolymer and ller backbones and participating in intermolecular hydrogen bonding. 30,33 Overall, our data are in line with the results obtained in other works (Table 2), demonstrating the potential of biopolymer coatings to improve the oxygen barrier properties of PET without jeopardizing its intrinsic optical properties.…”
Section: Optical Mechanical and Oxygen Barrier Properties Of Pet/bion...supporting
confidence: 92%
See 1 more Smart Citation
“…These results are supported by previous scientic research, [46][47][48] and ascribed to water molecules competing for the -OH groups displaced along both the biopolymer and ller backbones and participating in intermolecular hydrogen bonding. 30,33 Overall, our data are in line with the results obtained in other works (Table 2), demonstrating the potential of biopolymer coatings to improve the oxygen barrier properties of PET without jeopardizing its intrinsic optical properties.…”
Section: Optical Mechanical and Oxygen Barrier Properties Of Pet/bion...supporting
confidence: 92%
“…28,29 Conversely, our recent work involved a pullulan-based coating formulation reinforced with enzymatically derived BCNCs as organic nanollers, applied to bare polyethylene terephthalate (PET) substrate to enhance its barrier performance. 30 Remarkably, there are no existing works in the current literature that investigate the inuence of acid type on hydrolysis degree and structural characteristics of BCNCs intended for integration into biopolymeric matrices to enhance their inherent barrier properties. Hence, this study addresses, for the rst time, the development and application of a bionanocomposite coating formulation with low oxygen permeability attributes by utilizing acid-derived cellulose nanocrystals of bacterial origin (K. sucrofermentans).…”
Section: Introductionmentioning
confidence: 99%
“…This was confirmed by the observations of Tongnuanchan et al [19] and Yao et al [45], who reported a decrease in transparency for fish skin gelatin films incorporated with citrus EO and gelatinchitosan films supplemented with D-Limonene. From a practical point of view, the haze values recorded in our study for all the formulations were below a 3% value, which is the threshold to guarantee an adequate display of the product inside the package [46].…”
Section: Light Transmittance and Hazementioning
confidence: 68%
“…CBH mainly targets the crystalline region of cellulose, while GB hydrolyzes the chains into glucose sugars. 40 Enzymatic hydrolysis combined with the mechanical preparation of NC has been moving in a highly promising direction in recent years. To make enzymatic hydrolysis a more viable option for large-scale production, efforts should focus on overcoming its high cost.…”
Section: Biological Methodmentioning
confidence: 99%